P675 Associations between Inflammatory Bowel Disease, social isolation, and mortality: evidence from UK Biobank cohort study. (21st January 2022) - Chen, J; Geng, J; Wang, J; Fu, T; Sun, Y; Chen, H; Chen, X; Wang, X; Hesketh, T
Abstract: Background: Social well-being of patients with inflammatory bowel disease (IBD) is garnering increased attention; however, the impact of social isolation remains poorly understood. We investigated whether patients with IBD are at a higher risk of social isolation, and whether any such isolation is associated with increased mortality. Methods: We investigated 489, 731 participants from UK Biobank (including 5, 671 with IBD); the mean follow-up was 11.63 years. Diagnoses of IBD and its subtypes of Crohn's disease (CD) and ulcerative colitis (UC) were confirmed with the combination of self-reporting, primary care, and hospital admission data. Social isolation was measured by the frequency of meeting family/friends, leisure and social activity, and communal/solitary living. Mortality was ascertained through data linkage with national death registries. Logistic regression was used to calculate the association between social isolation and IBD. The association between social isolation and mortality was investigated using multivariable Cox regression models. Results: In the fully adjusted model, CD (odd ratio [OR]=1.24, 95% CI: 1.07, 1.42, P =0.003) was cross-sectionally associated with social isolation, whereas UC was not (OR=0.99, 95% CI: 0.89, 1.11, P =0.875). Social isolation was prospectively associated with an elevated risk of incident mortality among patients with CD (HR=2.09, 95% CI: 1.51, 2.89, P <0.001), but not among those with UC (HR=1.28, 95% CI: 0.94, 1.76, P =0.121). Data from subgroup and sensitivity analyses were consistent with those from the primary analysis. Conclusion: Patients with CD are more likely to be socially isolated. Socially-isolated patients with CD increases the risk of premature death.